WEB as a combined support and embolization device in a giant partially thrombosed donut-shaped aneurysm - Vollherbst, Dominik; Hohenstatt, Sophia; Schönenberger, Silvia; Bendszus, Martin; Möhlenbruch, Markus Alfred (Journal of clinical neuroscience, 2020)
Background: Giant partially thrombosed aneurysms are challenging lesions for which treatment can be difficult due to their unfavourable anatomical configuration and abnormal flow conditions. Case description: The patient presented in this report suffered from a symptomatic giant partially thrombosed donut-shaped aneurysm of the left-sided supraophthalmic internal carotid artery. Due to the location and the size of the aneurysm, endovascular treatment was performed. Navigation of the microcatheter-microwire-system distal to the aneurysm for stent deployment was technically not possible due to limited support, caused by the large aneurysm. Therefore, a WEB device was placed in the distal leg of the donut-shaped aneurysm. Additionally to the occlusion of this part of the aneurysm, the WEB device enabled enough support to navigate the microcatheter-microwire-system distal to the aneurysm. After deployment of a flow-diverting stent, coiling of the aneurysm was performed. Follow-up angiography showed complete occlusion of the aneurysm. The patient suffered from severe headaches which were no longer present 6 months after treatment. Conclusions: The WEB intraaneurysmal flow diverter can be effectively used as combined support and embolization device for the treatment of complex aneurysms in selective cases where other catheterization and embolization strategies have failed. (C) 2020 Elsevier Ltd. All rights reserved.
Gesehen am 18.05.2020